(untitled) ("Conference on Universal Science Research 2023", 2026)
This article examines the linguocultural and methodical foundations of teaching axiological units — value-laden words, phrases, and expressions — in English and Uzbek. Axiological units reflect the moral, ethical, and emotional values embedded in a language community’s worldview. The study identifies key differences and similarities in how values are linguistically encoded in both languages.